Shifting attention in visuospatial short-term memory does not require oculomotor planning: Insight from congenital gaze paralysis. (15th October 2021) - Masson, Nicolas; Andres, Michael; Carneiro Pereira, Sarah; Vandenberghe, Antoine; Pesenti, Mauro; Vannuscorps, Gilles
Abstract: Attention allows pieces of information stored in visuospatial short-term memory (VSSTM) to be selectively processed. Previous studies showed that shifts of attention in VSSTM in response to a retro-cue are accompanied by eye movements in the direction of the position of the memorized item although there is nothing left to look at. This finding raises the possibility that shifts of attention in VSSTM are underpinned by mechanisms originally involved in the planning and control of eye movements. To explore this possibility, we investigated the ability of an individual with congenital horizontal gaze paralysis (HGP2) to shift her attention horizontally or vertically toward a memorized item within VSSTM using a retro-cue paradigm. As efficient oculomotor programming is not innate but requires some trial and error learning and adaptation to develop, congenital paralysis prevents this development. Consequently, if shifts of attention in VSSTM rely on the same mechanisms as those supporting the programming of eye movements, then horizontal congenital gaze paralysis should necessarily prevent typical retro-cueing effect in the paralyzed axis. At odds with this prediction, HGP2 showed a typical retro-cueing effect in her paralyzed axis. This original finding indicates that selecting an item within VSSTM does not depend on the ability to program a saccade. Highlights: Shifting attention in visual short term memory is accompanied by eye movements. Shifting attention in visual short term memory was tested with a retro-cue task. It was suggested that eye movements are functional to these shifts. One individual with congenital gaze paralysis showed typical retro-cue effect. We show that eye movements are not functional to shift of attention in memory.